2020
DOI: 10.1007/s12020-020-02306-4
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Klotho: a possible predictor of quality of life in acromegaly patients

Abstract: Purpose Although quality of life (QoL) is improved in patients with acromegaly after disease control, QoL correlates only weakly with traditional biomarkers. Our objective is to investigate a potential relation between the new serum biomarker soluble Klotho (sKlotho), GH and insulin-like growth factor 1 (IGF-1) levels, and QoL. Methods In this prospective cohort study, we investigated 54 acromegaly patients biochemically well-controlled on combination treatment with first-generation somatostatin receptor ligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Other markers of GH action such as IGF binding protein 3 or acid-labile subunit have been suggested to assess discrepant GH and IGF-I results [ 46 ]. Soluble Klotho, predominantly expressed in the kidney [ 47 ], correlates with GH levels over a wide concentration range [ 48 ], and has been suggested to correlate with QOL improvements [ 49 ].…”
Section: Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Other markers of GH action such as IGF binding protein 3 or acid-labile subunit have been suggested to assess discrepant GH and IGF-I results [ 46 ]. Soluble Klotho, predominantly expressed in the kidney [ 47 ], correlates with GH levels over a wide concentration range [ 48 ], and has been suggested to correlate with QOL improvements [ 49 ].…”
Section: Assaysmentioning
confidence: 99%
“…Additional analyses of PAPE data focused on predictors of treatment benefit. Neither GH nor IGF-I correlated with improved QOL observed after switching combination therapy regimens [ 49 ]. Somatostatin receptor SST2, but not SST5, expression, correlated with lower IGF-I levels [ 89 ].…”
Section: Combination Therapy With Srl + Pegvisomantmentioning
confidence: 99%
“…In 33 of the 45 patients from the PAPE study, tumor volume decreased but this decrease was clinically significant (≥25%) in 15 cases only (33%) ( 36 ). In both treatment groups significant improvements in quality of life were observed after switching to pasireotide LAR ( 37 ). However, we should acknowledge that assessing a difference in quality of life between monotherapy and combination therapy was not a primary endpoint of this study, and it was underpowered to detect a significant difference.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that in all the remaining 4 discordant cases, where sαKL remained elevated after treatment, IGF-I also remained elevated (despite normal GH random ), and all 4 patients reported severe symptoms, including headache, and had a worse quality of life compared with patients with normal sαKL. This is of interest since a recent study ( 29 ) had reported that changes in sαKL during successful treatment correlate with improvements particularly in quality of life and headache. The mechanisms are unclear, but it seems that sαKL could have particular relevance as a biomarker of central effects of GH excess.…”
Section: Discussionmentioning
confidence: 98%